Existence and multiplicity solutions for discrete Kirchhoff type problems. (April 2022) - Long, Yuhua; Deng, Xiaoqing
Abstract: In this paper, we make use of minimax methods and invariant sets of descending flow to study superlinear discrete Kirchhoff type problems. We give two interesting results: one concerns the existence of a nontrivial solution and the other deals with multiple solutions which are composed of sign-changing solution, positive solution and negative solution.